(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article is devoted to the problem of study and comparison of the concepts of «розум/wit» and «дурість/stupidity» in conceptual aspect, which is in identification and description of a complex of language means, nominated concepts and their individual characteristics.